Botanical origin and compositional variability of bee-derived propolis in relation to current clinical evidence and nutraceutical applications - Kwanyong Choi; Ji Yeon Kim (Applied Biological Chemistry, 2026)
Abstract The clinical translation of propolis as a nutraceutical is complicated by substantial chemical variability associated with its botanical and geographical origins. This mini-review critically examines current human evidence on oral propolis supplementation, with particular attention to compositional variability, clinical phenotype, and methodological limitations. Recent clinical trials, conducted primarily with presumed temperate poplar-type propolis and Brazilian green propolis, have reported changes in selected inflammatory, oxidative, metabolic, renal, respiratory, and reproductive outcomes. These findings include reductions in hs-CRP, TNF-α, and markers of lipid peroxidation, although effects were not consistently observed across all outcomes, populations, or preparations. Considerable heterogeneity was also evident in extraction methods, intervention doses, treatment durations, chemical characterization, and outcome selection, limiting direct comparisons among studies and preventing reliable dose-response or chemotype-specific interpretations. In addition, many trials relied predominantly on surrogate biochemical or physiological markers rather than patient-centered clinical outcomes. In conclusion, the available evidence suggests preparation-specific and phenotype-aligned biological responses to oral propolis supplementation. Future studies should use chemically characterized and standardized preparations and evaluate clinically meaningful outcomes alongside relevant mechanistic markers.